Manajemen Kebijakan Fiskal: Strategi Penetapan Kosmetik sebagai Objek Cukai - Fachrudin, Mohammad; Muttaqien, Fauzan (DINASTI RESEARCH, 2024)
: The rapid growth of the cosmetics industry has raised concerns about health and environmental risks from chemicals like parabens and Sodium Lauryl Sulfate (SLS). Parabens disrupt endocrine functions, potentially causing hormonal imbalances and cancer, while SLS contributes to skin irritation and environmental pollution. This study examines the feasibility of imposing excise taxes on cosmetics containing these substances, using a descriptive qualitative approach that considers philosophical, legal, socio-economic, and operational aspects. The findings indicate that cosmetics with parabens and SLS are viable candidates for excise taxation. Philosophically, this aligns with the Pigouvian principle of internalizing social and environmental costs. Legally, these products qualify as excisable goods under existing laws. Socio-economically, excise taxes increase product prices, reducing consumption and encouraging a shift to safer alternatives. Producers are incentivized to use eco-friendly materials. International examples, such as the EU and ASEAN regulations on parabens, show the success of such policies. Operationally, technologies like blockchain can enhance supply chain transparency, while digital labeling informs consumers. Excise revenues could support health programs, environmental restoration, and research into safer ingredients. These measures would reduce risks and promote sustainable industry practices. The government should invest in surveillance and allocate excise revenues to maximize societal benefits.